Strategi Radio K-Lite Bandung Dalam Menyajikan Berita Untuk Mempertahankan Atensi Pendengar - Salman, Muhammad; Rosyidi, Imron; Dulwahab, Encep (Jurusan Ilmu Komunikasi, Fakultas Dakwah dan Komunikasi, UIN Sunan Gunung Djati Bandung, 2022)
This study aims to find out the strategy carried out by K-Lite 107.1 FM Radio in presenting news to maintain listeners' attention, especially in the Soft Sensation program amid the development of the digital era and its special segmentation. This research uses a qualitative approach and uses a constructivism paradigm as well as uses a descriptive study research method in which this research obtains the results of an in-depth process of presenting news strategies to maintain listeners' attention on the Soft Sensation program. In this study it was found that the strategy carried out by K-Lite 107.1 FM Radio to maintain listeners' attention was by carrying out citizen journalism activities, because it involved listeners in the process of presenting, writing and news presentation policies on the Soft Sensation program.